Snag distributions in relation to human access in ponderosa pine forests - Jeff P. Hollenbeck; Lisa J. Bate; Victoria A. Saab; John F. Lehmkuhl (Wildlife Society Bulletin)
Abstract Ponderosa pine (Pinus ponderosa) forests in western North America provide habitat for numerous cavity‐using wildlife species that often select large‐diameter snags for nesting and roosting. Yet large snags are often removed for their commercial and firewood values. Consequently we evaluated effects of human access on snag densities and diameter‐class distributions at nine locations in ponderosa pine forests throughout the interior western United States. We found no relationship between small‐diameter (23–50 cm diam breast ht [dbh]) snags and human access measures (i.e., road density, distance to nearest town, and topography). However, large‐snag (≥50 cm dbh) density was best predicted by road density, which suggested a decline, on average, of 0.7 large snags/ha for every km of road/km2. Most locations had relatively high densities of small‐diameter snags (<23 cm dbh) and diminishing density as diameter class increased. Idaho and Colorado study locations had higher snag densities in the largest diameter classes compared with remaining locations. These locations experienced minimal commercial timber harvest, were situated far from towns, and had few or no roads. Persistence of large‐diameter snags and adequate snag densities for wildlife requires consideration of human access characteristics at coarse spatial scales. Snag management guidelines may need to incorporate these measures and focus more on retention of large‐diameter snags than minimum density targets. © 2013 The Wildlife Society.